College aspirations, gender sexuality alliances, and teacher support among diverse LGBTQ youth. Issue 2 (23rd February 2022) - Feldman, Steven; Watson, Ryan J.; Gallik, Connor
ABSTRACT: Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) youth report hostile school climates and sexuality-based harassment, but scholarship has not clearly documented how these climates might be associated with college aspirations among this population. Given college has become a common aspiration for many high school youths, we sought to explore subgroup differences in college aspirations among LGBTQ youth, and whether or not LGBTQ-specific community factors, such as Gender Sexuality Alliances (GSA) presence and teacher support, were related to college aspirations. To do this, we analysed a large sample (N = 11, 327, Mage = 15.57) of LGBTQ youth from across the United States. We compared college aspirations across subgroups of youth via bivariate and multivariable logistic regression models to explore how school factors (i.e., presence of GSAs and LGBTQ-specific teacher supportiveness) were associated with college aspirations among LGBTQ youth. We found that transgender youth were less likely to aspire to go to college compared to cisgender counterparts. Additionally, more common sexual minority subgroups (e.g., gay/lesbian) were less likely to aspire to go to college compared to their counterparts with more emergent identity labels (e.g., asexual, queer). The presence of GSAs and higher reports of LGBTQ-supportive teachers were associated with increased odds of aspiring to go to college across all LGBTQ youth in our sample. These findings have implications for how schools and teachers prepare sexual and gender minorities for college. The findings imply that LGBTQ populations should not be treated as monolithic in their college readiness, preparation, and aspirations.